1970
DOI: 10.3329/bjvm.v6i1.1338
|View full text |Cite
|
Sign up to set email alerts
|

Population density of helminths in ducks: effects of host’s age, sex, breed and season

Abstract: A study was conducted to investigate the population density of helminth parasites in domestic ducks (Anas boschas domesticus) in relation to host's age, sex, breed and seasons of the year from March 2002 to May 2003. A total of 300 ducks were collected from different villages of Netrokona and Mymensingh districts of Bangladesh and autopsied to collect the parasites and counted to determine the population density of parasites. Off 300 ducks examined, 290 (96.66%) were infected with 17 species of helminth parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
4
7
0
Order By: Relevance
“…The finding is similar to that of Musa et al (2012). Farjana et al (2008) found higher mean density of all parasites in female ducks (31.35 ± 4.72) than males (27.52 ± 3.32). Among the Raillietina spp., Raillietina echinobothrida was equally prevalent in male and female (50%).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The finding is similar to that of Musa et al (2012). Farjana et al (2008) found higher mean density of all parasites in female ducks (31.35 ± 4.72) than males (27.52 ± 3.32). Among the Raillietina spp., Raillietina echinobothrida was equally prevalent in male and female (50%).…”
Section: Resultssupporting
confidence: 88%
“…Usually snails are available in monsoon when ducks are feed on snails, get infected with metacercaria of trematodes, but usually trematodes take some time to become adult in final host (Farjana et al 2008). Parasite prevalence was comparatively low in winter for all the parasite species found (Table 4).…”
Section: Resultsmentioning
confidence: 97%
“…Hymenolepis columbae showed highest prevalence in the present study which is consistent with the study of Farzana et al (1) . Soulsby (11) found thousands of hymenolepids per bird.…”
Section: Namesupporting
confidence: 83%
“…In the present study female had higher prevalence and intensity of parasite infection. This is consistent with the study of Farzana et al (1) where they found high density of parasitic infection in female ducks compared to male. Female ducks may be more susceptible to parasitic infection due to egg laying and also lack of balanced nutrition, which affect their immune system and ability to combat the parasitic infection.…”
supporting
confidence: 83%
“…Regular use of anthelmintics (p value = 0.001), treatment of diseased duck (p = 0.024), providing supplementary feed ingredients (p= 0.004) and presence of marshy lands (p =0.009) were positively associated with higher egg production. Anthelmintics reduce the burden of parasites and thus the nutrients are more utilized for egg production [11] .…”
Section: Factors Associated With Productive Performance Of Ducksmentioning
confidence: 99%